Romeo and Juliet’s Rewriting in the Walt Disney Animated Movie Pocahontas: Adaptation Studies, Comparative Literature and Theory of Intertextuality - Tiago Marques Luiz (Cadernos de Tradução, 2023)
Intertextuality has been a driving force for Adaptation Studies, but few scholars have highlighted its relevance, rather prioritizing issues such as audience reception, cinematographic technique or aesthetics and, occasionally, fidelity. However, the starting point for any audiovisual production (be it film, television or theater) is the written matter, the text. Inserted within the field of Adaptation Studies in dialogue with Comparative Literature and Theory of Intertextuality, the present papers assesses the extent to which there are points of contact between William Shakespeare’s tragedy Romeo And Juliet the Walt Disney animated motion picture Pocahontas. The paper initially discusses the adaptation of Shakespeare’s text as a starting point for film productions, proceeding to theoretical reflections between Comparative Literature, Adaptation Theory, intertextuality and rewriting, and to the comparative analysis between the tragedy and the motion picture, which leads to the conclusion of a retroversive movement between source and adapted texts, which invites to the question of intertextual rewriting in Adaptation Studies